(untitled) (Publicaciones en Ciencias y Tecnología, 2013)
This research analyze the distinctive features of technology management in business for the retail, service and manufacturing / industrial sector, located in Barquisimeto - Lara state / Venezuela. The current situation of the companies in their technological management practices, and the constraints they face for their execution are evaluated. It is a descriptive research with a field design. The sample consisted of 60 companies (12 retail, 20 service and 28 manufacturing / industrial sector). The instrument applied consists in closed questions considering the Likert scale, complemented with other open questions, where interviewed managers gave their opinions and perceptions. It is concluded that managers possess Technology Management knowledge, and even consider it as an important aspect in the current economy. However, very few actions have taken place in this area, leading to a lack of the attention that this matter really deserves, Technological capability is deficient due to the absence of research on technological requirements of the companies, and the excess of routine activities prevents the insertion of innovation processes and technologies in companies.